The impacts of green LaBSiO5: Tb3+, Ce3+ phosphor on lumen output of white LEDs - Ha Thanh Tung; Huu Phuc Dang; Phung Ton That (Bulletin of Electrical Engineering and Informatics, 2023)
The traditional solid-state technique was used to create LaBSiO5 phosphors doped with Ce3+ and Tb3+ at 1,100 °C. These phosphors' phase purity and luminous characteristics are looked at. Under ultraviolet (UV) light stimulation, LaBSiO5: Tb3+ phosphors emit bright green light, whereas LaBSiO5 samples incorporated with Ce3+ emit blue-violet light. With UV ray stimulation, LaBSiO5 samples incorporated with Ce3+ as well as Tb3+ emit blue-violet as well as green illumination. The 5d-4f shift for Ce3+ is responsible for the blue-violet radiation, while the 5D4→7F5 transition of Tb3+ is responsible for the green radiation. The mechanism for power conversion between Ce3+ and Tb3+ was examined since there is a spectral overlap among the stimulation line for Tb3+ and the emitting line for Ce3+.